2006
DOI: 10.1194/jlr.m600150-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Rat long-chain acyl-CoA synthetase mRNA, protein, and activity vary in tissue distribution and in response to diet

Abstract: Distinct isoforms of long-chain acyl-CoA synthetases (ACSLs) may partition fatty acids toward specific metabolic cellular pathways. For each of the five members of the rat ACSL family, we analyzed tissue mRNA distributions, and we correlated the mRNA, protein, and activity of ACSL1 and ACSL4 after fasting and refeeding a 69% sucrose diet. Not only did quantitative real-time PCR analyses reveal unique tissue expression patterns for each ACSL isoform, but expression varied markedly in different adipose depots. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
137
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 31 publications
10
137
1
1
Order By: Relevance
“…Yao and Ye (18) found that ACSL3 mediates the synthesis of phosphatidylcholine that is necessary for the assembly of very low density lipoprotein in human hepatoma cell lines. Also recent animal studies demonstrated that expression of mRNA of ACSL3 was down-regulated in 48-h-fasted rats (16). Taken as a whole, these data strongly support a synthetic role of ACSL3 in energy metabolism.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Yao and Ye (18) found that ACSL3 mediates the synthesis of phosphatidylcholine that is necessary for the assembly of very low density lipoprotein in human hepatoma cell lines. Also recent animal studies demonstrated that expression of mRNA of ACSL3 was down-regulated in 48-h-fasted rats (16). Taken as a whole, these data strongly support a synthetic role of ACSL3 in energy metabolism.…”
Section: Discussionsupporting
confidence: 65%
“…ACSL3 has a broad range of substrate preferences toward C 16 -C 24 fatty acids (35,37). Although few studies have focused on the physiological function of ACSL3 (16,35), its localization on lipid droplets or endoplasmic reticulum membranes (31,32) suggests that this enzyme is likely involved in lipid synthesis. Proteomic analyses have revealed that ACSL3 is located on the surface of lipid droplets and is physically associated with lipid droplets fractions in 3T3-L1 adipocytes (32), human hepatocytes (31), and A431 human epithelial cells (38).…”
Section: Discussionmentioning
confidence: 99%
“…Acsl4 Knockdown Reduced Both GSIS and FA-augmented GSIS-Given the substrate preference and tissue distribution of Acsl4 (32,33), we evaluated the effect of Acsl4 knockdown on insulin secretion. In the presence of various secretagogues, including glucose, specific fatty acids, and KCl, knockdown of Acsl4 expression significantly reduced insulin secretion (Fig.…”
Section: Acsl5 Sirna Suppresses Acsl5 Mrna and Protein But Doesmentioning
confidence: 99%
“…ACSL1 is the abundant isoform in major metabolic tissues, including liver, heart, adipose, and muscle. Whereas in vitro studies carried out in different cell lines have reported similar as well as conflicting functions of ACSL1 in mediating FA oxidation, FA uptake, and triglyceride (TG) synthesis (9,11,13), recent animal studies with tissue-specific knock-out of Acsl1 revealed some definitive functions of this enzyme. In heart and adipose tissues, Acsl1 deficiency generated a profound decrease in FA oxidation without an impact on [ 14 C]oleate incorporation into TG or phospholipid (14,15).…”
mentioning
confidence: 99%
“…These isoforms differ substantially in their substrate preference, tissue distribution, and subcellular compartmentation as well as in their responses to nutritional status (9), all of which contributes to the unique functions of each isoform in a particular tissue or a cell type.…”
mentioning
confidence: 99%